2020
DOI: 10.1080/23802359.2020.1790318
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of melon fly, Zeugodacus cucurbitae (Diptera:Tephritidae) from Kunming, Southwest China and the phylogeny within subfamily Dacinae

Abstract: The melon fly, Zeugodacus cucurbitae (Diptera:Tephritidae) is an important invasive pest and distributed throughout tropical, subtropical countries and areas. In this study, we report the complete mitochondrial genome of the fly with 15, 685 base pair in length, which includes 37 genes (the large and small ribosomal RNA subunits, 22 transfer RNA genes, 13 genes encoding mitochondrial proteins) and a noncoding A þ T-rich control region. Molecular phylogeny indicated that there was a high bootstrap value support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…In the present study, the phylogenetic relationships within Tephritidae can be presented as follows: ((Bactrocera, Dacus, Zeugodacus), Felderimyia, Anastrepha), (Acrotaeniostola, (Neoceratitis, Ceratitis), Euleia, Rivellia), (Procecidochares, (Tephritis, Sphaenisscus))))), in concordance with the findings of previous phylogenetic studies [23,24,63,64]. The results showed that four genera (Felderimyia, Zeugodacus, Dacus and Bactrocera) are closely related and they gathered to form a sister group.…”
Section: Disscusionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the phylogenetic relationships within Tephritidae can be presented as follows: ((Bactrocera, Dacus, Zeugodacus), Felderimyia, Anastrepha), (Acrotaeniostola, (Neoceratitis, Ceratitis), Euleia, Rivellia), (Procecidochares, (Tephritis, Sphaenisscus))))), in concordance with the findings of previous phylogenetic studies [23,24,63,64]. The results showed that four genera (Felderimyia, Zeugodacus, Dacus and Bactrocera) are closely related and they gathered to form a sister group.…”
Section: Disscusionsupporting
confidence: 92%
“…The complete mitogenome of S. atilius was a circular, double-stranded DNA molecule with a total length of 16, 854 bp, which was similar to that of other Tephritoidea insects analyzed, ranging from 15,117 bp (Tephritis femoralis) to 16,739 bp (Anastrepha fraterculus) (Table 1). It has the typical organization and composition of an insect mitochondrion, containing 37 genes, including 13 protein-coding genes (PCGs), 22 tRNA genes, and 2 rRNA genes, which was consistent with those described in other subfamily Tephritoidea insects, such as Bactrocera carambolae [22], Zeugodacus cucurbitae [24], Dacus haikouensis [40]. The nucleotide composition of all regions showed a strong AT bias [41], as seen in other insects [18,19,42].…”
Section: Disscusionsupporting
confidence: 78%
See 2 more Smart Citations
“…Zeugodacus cucurbitae Coquillett, also known as the melon fly, is an economically important pest species that is found throughout subtropical and tropical regions. 1 While Z. cucurbitae can attack roughly 130 host plants, snap melons, musk melons, and bitter gourds are their preferred hosts. 2 Owing to their highly destructive, invasive, polyphagous characteristics, Z. cucurbitae are considered to be a critical quarantine pest.…”
Section: Introductionmentioning
confidence: 99%